2010
DOI: 10.1111/j.1469-7610.2010.02276.x
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of antisocial behaviour towards siblings predict antisocial behaviour towards peers

Abstract: These findings highlight the importance of a developmental perspective when examining antisocial behaviour between young siblings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 45 publications
1
47
0
1
Order By: Relevance
“…Current evidence suggests that those who are both bullied at home and at school have highly increased emotional problems, likely because they have no safe place and thus no respite from bullying. Where investigated, there is a suggestion that early sibling aggression and bullying is a precursor of adverse relationships with peers 75 . Thus, if one wants to prevent sibling bullying and peer bullying, intervention has to start at home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current evidence suggests that those who are both bullied at home and at school have highly increased emotional problems, likely because they have no safe place and thus no respite from bullying. Where investigated, there is a suggestion that early sibling aggression and bullying is a precursor of adverse relationships with peers 75 . Thus, if one wants to prevent sibling bullying and peer bullying, intervention has to start at home.…”
Section: Discussionmentioning
confidence: 99%
“…One innovative study combined direct observation of sibling directed antisocial behaviour in the family's homes at 3 and 6 years and interaction of unfamiliar peers in an experimental setting 75 . Antisocial behaviour between siblings was observed at home when the children were 3 and 6 years old, and at 6 years they were invited to the laboratory where they were paired with two other unfamiliar children for a triadic play situation.…”
Section: Sibling Bullying -Is There a Link To Peer Bullying?mentioning
confidence: 99%
“…Similarly, children who perpetrate aggression towards their siblings more often report being peer bullies or bully-victims (Duncan, 1999;Menesini et al, 2010). Although much of this research is cross-sectional, an experimental study among young children found that aggression towards siblings is predictive of bullying of peers one year later within a laboratory setting (Ensor et al, 2010).…”
Section: Sibling Aggression and Peer Bullyingmentioning
confidence: 99%
“…Time spent together leads to familiarity that can breed contempt. This means they know exactly how to provoke or upset their siblings (17) . Sibling interactions are emotionally charged relationships defi ned by strong, uninhibited emotions of positive, negative, and sometimes ambivalent quality (7) .…”
Section: Sibling Bullyingmentioning
confidence: 99%
“…Others report that between 30 % and 98 % are physically attacked or victimized by their siblings during a year (16) . In many families aggression between siblings is frequent and a source of great concern to parents (17). Similarly, up to a quarter of children become victims of violence from nonsibling peers, most frequently at school (18) .…”
Section: Introductionmentioning
confidence: 99%